Serial Excision- an Aesthetically Pleasing Way for Removal of Large Cutaneous Lesions on the Face - Minu, Firdous Quader; Rahman, Muhammad Hasibur; Ali, Rubaiya; Asifuzzaman, Md; Siddiky, Sayeed Ahmed (Community Based Medical Journal, 2013)
Face is a very prominent part of our body. It is the first feature that we notice when we meet someone. When there is a large cutaneous lesion /scar on the face it stands out, and can make a person very self conscious. So it becomes a source of concern and embarrassment for the person involved. As such when a patient with this type of problem presents to a cosmetic surgeon, he has to take great care as to how it can be removed and what will be the aesthetic outcome of the treatment. This is especially important if the patient is young. Different types of flaps like nasolabial flaps, forehead flaps, deltopectoral flaps etc. are commonly used for reconstruction of defects following excision of large lesions. Sometimes tissue expanders are also used. Of course skin grafting is probably the easiest way to cover large areas when flaps cannot be used. But all of these procedures leave big scars which are often not acceptable to the patients. We have found that serial excision is a good way of removal of large lesions or scars especially when it involves the face. Although the patient needs two or more sittings for completion of the procedure, the final outcome is much more acceptable to the patient. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13823 Community Based Medical Journal Vol.1(1) 2012 14-16